Effect of seated leg press exercise on knee extension strength in elderly - Karar Khoga Naamat; Heydar Sadeghi; Mansour Sahebozamani; Somaye Nazari (Vesnu Publications, 2014)
Abstract Introduction: After age 50 to 70 years, 15% of muscles strength is lost per decade. Elderly people need to 90% of knee extensor muscles strength for daily activities such as getting up from a chair, while this value is only slightly more than half in young people. Due to the importance of knee extensor muscles strength in elderly, the purpose of this study was effect of seated leg press exercise on knee extension strength in elderly. Materials and Methods: twenty-four elderly men (age 61.41±6 years, height 75.9±6.2 kg and weight 173.31±5.2) were randomly divided in two matched groups. Resistance training group performed one set of 12 repetitions with 70% of one repetition maximum (1RM) in each session, twice a week for eight weeks. Control group were engaged in their daily activities in this period. Isokinetic strength of the knee extensors of both legs was determined at 60°/s with a dynamometer (Biodex system 3). Results: The 8-week seated leg press exercise led to significant improvements in knee extension strength from pretest to posttest for both dominant and non-dominant leg in resistance training group  (respectively P=0.002 and P=0.003). These changes were not significant in control group (respectively P=0.220 and P=0.168). Conclusions: performing one set of 12 repetitions with 70% of 1RM in each session, twice a week for eight weeks, may led to significant improvement in knee extension strength in elderly people. Key words: Seated leg press, Knee extension strength, Elderly